The Urgency Of The Imposition Of Value Added Tax (Vat) On Digital Products With The Type Of Smartphone Applications In The Era Of The Industrial Revolution 4.0 - Alviona Anggita Rante Lembang (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2021)
The current era of globalization makes Indonesia can easily develop to compete with other countries. Until now, Indonesia is occupying the Industrial Revolution Era 4.0 so that public awareness and appreciation is needed. The application growth, which is already high and widely used by the public, is considered to be a new source of income for the state. Due to the growth of applications and their increasing number of users, smartphone applications have become public consumption, so they can be included as objects of Value Added Tax (VAT). The imposition of VAT on smartphone applications can greatly increase state revenues due to the very high number of smartphone users in Indonesia. Through the results of this study, VAT on smartphone applications is considered to be effective if it can be used as a means to increase state income and create justice for all business actors, both conventional and digital.